Molecular disruption through acid injection into waste activated sludge – A feasibility study to improve the economics of sludge dewatering. (1st March 2018) - MacDonald, Brittany A.; Oakes, Ken D.; Adams, Michelle
Abstract: Industrial productivity is often judged solely by the primary product's marketability, while opportunities for secondary products derived from process by-products are often overlooked. In paper mills, large volumes of moisture-rich paper mill residuals (cellulose sludge) are produced, for which commercial use is currently difficult. Port Hawkesbury Paper LP, Port Hawkesbury, Nova Scotia, produces over 7 t/hr of waste sludge with a seasonally-dependent dryness ranging from 25 to 38% (w/w). Various chemical or mechanical dewatering options exist; however, knowledge of the unique sludge composition and properties is essential to predicting how the product will react under each method. Sonication, Fournier rotary press technology, freeze/thaw cycling, and gravity drying were among the dewatering opportunities briefly explored outside of the chosen method, acidification. Notably, many industries utilizing dewatering technologies may not be producing value-added by-products, while geographic and climatic placement may limit processes which are possible for others. In the present study examining enhanced end-use value, further dewatering occurred through a comparative in situ experiment contrasting sulfuric acid and ferric sulfate acidification (direct acid injection into sludge). While both proton donors acidified the sludge and decreased moisture content, sulfuric acid was the more cost-effective option, yielding an ∼4% increase in dryness, with commensurate economic and environmental benefits. Highlights: Methods for dewatering waste pulp and paper mill sludge are proposed. Acid injection ruptures water-containing molecules. Use of thickening chemicals reduced due to increased ease of dewatering. Local paper mill used for generating industry applicable data. 93% sulfuric acid deemed best dewatering agent based on economics and performance.